Belt Road Initiative in the Simulacra Analysis (Indonesia - China Relationship in the Perspective of Indonesian Students in Nanjing City) - Dani Fadillah (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2020)
The research analyzed the perspectives of Indonesian students that were located in Nanjing by using Jean Baudrillard's theory of simulacra. Recently, China had been trying to revive the silk road, a line connecting the world through trade, that used to be gainful in the past, with a route called the belt road initiative. This program had unlocked China's cooperation gates with many other countries from all over the world, although much undesirable information circulated regarding this initiative, ranging from environmental issues to rumor on the sovereignty of the state of China’s partner. Through simulacra’s logic, the author outlined the perspective of Indonesian students that had studied in Nanjing, China, towards the belt road initiative. The research found that even though the students had long felt education in China and assimilated much knowledge about this country quite first-hand, they did not necessarily believe that this new route would benefit their homeland.